Je objektivnější shluková nebo faktorová analýza? : na příkladu atletického desetiboje - Ryba, Jiří (Optimální působení tělesné zátěže a výživy, 2006)
On the basis of analyse results of athletic decathlion we want to show more substantial statistical objectivity factor analysis in comparsion with cluster analysis. Factor analysis presets even after the rotation the same results. Bath actions is necessary completes the characterizations mather-of-fact signification.
Keywords: Men; Running; Track and Field; Humans; běh; shluková analýza; lidé; Efficiency; výkonnost; Cluster Analysis; Kinesiology, Applied; muži; Factor Analysis, Statistical; lehká atletika; faktorová analýza statistická; kineziologie aplikovaná